Effect of Allium sativum methanol extract in amelioration of arsenic-induced toxicity in Swiss albino mice - Raushanara Akter; Sharmind Neelotpol; Md. Tanvir Kabir (Phytomedicine Plus, 2022)
Background: : Arsenic (As) toxicity is a major public health concern in many countries worldwide. Chronic arsenic toxicity results in multiple organ failure, cancer, neurological disorder, behavioral disorder, reproductive complications, etc. Allium sativum (garlic) has been reported to ameliorate mercury, lead, and cadmium-induced toxicity previously. Purpose: : This research was aimed to evaluate the effect of methanol garlic extract in the amelioration of arsenic toxicity in Swiss albino mice. Methods: : Initially 36 Swiss albino mice were divided into 6 different groups such as control group, arsenic-treated group where dose of arsenic was 0.0075 mg/mL, and arsenic plus methanolic extract of garlic treated group, and mice were treated at three different doses of extract; 150, 300, and 500 mg/kg for 8 weeks. Finally, the change in body weight, hematological, and biochemical parameters were measured. Results: : Progressive body weight increase was observed in the control and only extracts treated groups whereas retardation of the body weight gain was found in the arsenic treated group. A decrease in the body weight gain was retarded in the groups that received arsenic plus garlic extract (GE). Compared to control, neutrophil (NEU), and eosinophil (EOS) counts as well as alanine aminotransferase (ALT), alkaline phosphatase (ALP), creatinine (CRE), and serum glutamic-pyruvic transaminase (SGPT) levels were increased whereas white blood cell (WBC), red blood cell (RBC), lymphocyte (LYM), and monocyte (MON) count were decreased in the arsenic-treated group. All these parameters were returned to normal levels in the garlic methanol extract-treated group. Conclusion: : This study suggests that garlic has the potential for depleting arsenic-induced toxicity and thus, dietary intake of garlic might have therapeutic benefits in the prevention or amelioration of arsenic-exposed toxicity.